A música como mediadora na formação da cidadania planetária: um estudo de caso numa escola da educação infantil na cidade de Picos-PI - Lima, Fabrícia Maria de Macêdo (2023)
The present study has as its theme "Between letters and melodies: Music as a mediator in the formation of planetary citizenship". In view of this, it can be highlighted that education based on a Planetary Citizenship perspective refers to several factors and possibilities, in which the planetary wellbeing is sought after through the conscious action of human beings and their relationship with the social environment of which they are a part. The research was carried out in a kindergarten school of the municipal education system in the city of Picos-PI. We included in the research only the pre- school teachers, with an age range of 4 and 5 year old children, in order to broaden the discussion on the subject. In view of all the information contained in this study, we can conclude that musicalization is an intervention strategy that can facilitate the integral formation of the child. The observation of the child's spontaneity in front of music can provide excellent material for the study of their cognitive, affective, and motor development, just as indifference to musical stimulation can be a concrete and significant reaction to an unsatisfactory situation. Music education is, therefore, faced with a challenge that, without a doubt, presents itself as primordial for an effective and consistent practice of the inclusion of music in the routine of Children's Education. It can be seen that the school effectively includes music in the school planning and pedagogical practice in Early Childhood Education, favoring the effective psychomotor, cognitive, and social development of the students, as well as the full construction of a planetary education.